1384. NSTI Outcomes with and without Hyperbaric Oxygen Therapy. (15th December 2022) - Shishido, Akira A; Vostal, Alexander C; Tripathi, Ravi; Uehling, Megan; Chintalapati, Sai Pavan Kumar; Conway, Lauren; Kus, Nicole J; Schrank, Gregory M; Rabinowitz, Ronald; DiChiacchio, Laura
Abstract: Background: Necrotizing soft tissue infections (NSTI) are characterized by fulminant tissue destruction and high mortality rates. Primary treatment is surgical debridement and antibiotics; hyperbaric oxygen therapy (HBOT) may be considered as adjuvant therapy. HBOT for NSTI remains controversial given the lack of quality evidence. HBOT is frequently used for NSTI at our institution; however, the early COVID-19 pandemic forced a significant decrease in its utilization. This practice change created an unusually high proportion of NSTI patients who did not receive HBOT at our institution and thus provided an opportunity to compare outcomes amongst NSTI patients who received HBOT against those who did not. Methods: We performed a retrospective cohort study of patients aged 18 years and older admitted with the diagnosis of NSTI between January 2018 and December 2020, a period that included the first 6 months of the pandemic (Figure 1). We collected data on patient demographics, comorbidities, infection location, pathogen, severity of illness (APACHE II score), whether HBOT was provided and number of dives. Outcomes included 90-day mortality, amputations, inpatient antibiotic days, ventilator days, and hospital length of stay. Figure 1 Proportion of NSTI patients admitted to R Adams Cowley Shock Trauma Center who received HBOT between January 2018 through December 2020. Proportions were averaged over six month blocks. Results: 253 patients were included of whom 143 (56%) received HBOT and 110 (43.3%) did not. Baseline characteristics were similar between the groups except for Wound Surface Area (WSA) and APACHE II score (Table 1). Length of stay was significantly longer in HBOT patients (15.3 days vs 11.7 days p=0.005, Table 2). Fewer HBOT patients had amputations (7.5% vs 21% p=0.007) and fewer died within 90 days of admission (6.3% vs 14.5% p=0.029). When stratifying patients by APACHE II score, HBOT patients with APACHE II scores > 18 had significantly lower mortality than non-HBOT patients (9.7% vs 32.4% p=0.035). Conclusion: In this population of NSTI patients who underwent surgical debridement, HBOT was associated with lower incidence of amputation, and lower mortality. Patients with APACHE II scores >18 who received HBOT had lower mortality than those who did not. A prospective study should further evaluate the impact of HBOT on mortality and amputations. Disclosures: All Authors : No reported disclosures.